Relevansi Pemikiran Pendidikan Abdullah Nashih Ulwan dalam Pendidikan Islam Kontemporer - Yumni Febriani Tanjung; Yusnidar Gea; Azizah Hanum OK (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the Islamic education thought of Abdullah Nashih Ulwan, a 20th century educational figure who is influential in the development of contemporary Islamic education. Ulwan offers a holistic concept of education by emphasising the cultivation of tawhid, noble character, balance, and the important role of parents and teachers. The research method used is a literature study by analysing Ulwan's main work,